1997
DOI: 10.1006/dbio.1997.8741
|View full text |Cite
|
Sign up to set email alerts
|

Germ-Layer Surface Tensions and “Tissue Affinities” inRana pipiensGastrulae: Quantitative Measurements

Abstract: The morphogenetic properties causing germ-layer spreading and stratification in amphibian gastrulation were called "tissue affinities" by Holtfreter. The differential adhesion hypothesis (DAH) attributes such liquid-like tissue rearrangements to forces generated by intercellular adhesions within and between the migrating cell populations. This theory predicts that, among the primary germ layers, the cohesiveness of deep ectoderm should be the greatest, that of deep mesoderm should be intermediate, and that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…Accordingly, it is possible to more directly compare the behavior of zebrafish mesendoderm and ectoderm in vivo by investigating their interaction in vitro. Only one paper currently exists (utilizing frog tissues) that explores how differential adhesion can specify sorting and envelopment of germ layer tissues (Davis et al, 1997). In that study, observations very similar to those presented here were reported.…”
Section: Discussion Tissue Surface Tensions Correlate With In Vitro Ssupporting
confidence: 74%
See 1 more Smart Citation
“…Accordingly, it is possible to more directly compare the behavior of zebrafish mesendoderm and ectoderm in vivo by investigating their interaction in vitro. Only one paper currently exists (utilizing frog tissues) that explores how differential adhesion can specify sorting and envelopment of germ layer tissues (Davis et al, 1997). In that study, observations very similar to those presented here were reported.…”
Section: Discussion Tissue Surface Tensions Correlate With In Vitro Ssupporting
confidence: 74%
“…The analysis of surface tension and sorting/envelopment behavior of germ layer progenitor cells in amphibians (Davis et al, 1997) and teleosts (this study) suggests that differential adhesion is involved in guiding germ layer morphogenesis during gastrulation. To determine whether differences in tissue surface tension directly influence sorting behavior, we altered the adhesive relationship of one of the germ layer progenitors and explored effects on surface tension and on sorting/envelopment behavior.…”
Section: Downregulation Of E-cadherin-based Cohesivity In the Ectodermentioning
confidence: 72%
“…Malcolm Steinberg's group performed a number of experiments [9,14,15], where they compressed cell aggregates of embryonic tissues between two parallel plates and measured the force required to keep the plates at a given separation. The purpose of these experiments was to show that the cells behave as viscoelastic liquids and to measure the surface tension of these embryonic tissues, and thus get a measure of cell-cell adhesion strength.…”
Section: Resultsmentioning
confidence: 99%
“…Cell tracking in vivo and in vitro highlights (i) largescale flows, (ii) exchange of nearest neighbors in a cellular aggregate, and (iii) rounding-up and fusion of aggregates (1). Macroscopic rheological properties such as surface tension can be measured using a tissue surface tensiometer (TST) (1)(2)(3)(4)(5)(6)(7)(8) or micropipette aspiration (9), and surface tension can be used to explain tissue self-organization in embryogenesis (8,(10)(11)(12) or cancer (13,14). In particular, cell sorting and tissue spreading can be explained in terms of tissue surface tensions that differ among cell types (1, 3-5, 8, 15, 16).…”
mentioning
confidence: 99%
“…One, the differential adhesion hypothesis (DAH), postulates that in analogy to ordinary fluids, tissue surface tension is proportional to the intensity of the adhesive energy between the constituent cells, which are treated as point objects. The DAH has proven successful in a variety of studies with cell lines (2)(3)(4)(5)15) , malignant (13,14) and embryonic tissues (1,5,8,16) and is widely accepted (12,17). A recent study by Foty and Steinberg (18) experimentally verified a linear relationship between adhesion molecule expression levels and tissue surface tension.…”
mentioning
confidence: 99%